Caspase‐7 participates in differentiation of cells forming dental hard tissues. (29th May 2013) - Matalova, Eva; Lesot, Herve; Svandova, Eva; Vanden Berghe, Tom; Sharpe, Paul T.; Healy, Christopher; Vandenabeele, Peter; Tucker, Abigail S.
Abstract : Apoptosis during tooth development appears dependent on the apoptotic executioner caspase‐3, but not caspase‐7. Instead, activated caspase‐7 has been found in differentiated odontoblasts and ameloblasts, where it does not correlate with apoptosis. To further investigate these findings, the mouse incisor was used as a model. Analysis of caspase‐7‐deficient mice revealed a significant thinner layer of hard tissue in the adult incisor. Micro computed tomography scan confirmed this decrease in mineralized tissues. These data strongly suggest that caspase‐7 might be directly involved in functional cell differentiation and regulation of the mineralization of dental matrices.